Graphite electrode and preparation method thereof
By pretreating carbon nanotubes, their dispersion and surface activity are improved, and they are coagulated and coated with graphite, the problem of graphite electrodes being easily degraded in high-temperature oxidation environments is solved, and their physical and chemical properties are significantly improved, and their service life is extended.
Patent Information
- Application Number
- CN202311365982.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
Graphite electrodes are prone to oxidation degradation in high-temperature oxidation environments, reducing their durability, and poor performance of large current discharge. Co-embedded with solvent during the first charge and discharge leads to shedding, reducing the motor life.
By pretreating the carbon nanotubes, including mixing the shock treatment with the solvent, removing part of the solvent and plasma equipment, the dispersion and surfactivity of the carbon nanotubes are improved, thereby coagulating with the graphite and coating to form a graphite electrode.
The crystallinity content of graphite electrodes is improved, its physical and chemical properties are enhanced, the internal resistance of the electrode is reduced, the uniform distribution of current is promoted, the service life of the electrode is extended, and safety hazards are reduced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphite electrodes, and in particular relates to a treatment process, a treatment system and an application of shale gas fracturing flowback fluid. Background Art
[0002] Graphite electrode is undoubtedly the most widely applicable and mature negative electrode material. It is low-cost and high-temperature resistant graphite conductive material. It is widely used in arc steelmaking and ore-fired electric furnaces and has attracted much attention. However, its high-current discharge performance is poor and its compatibility is poor. The co-embedding of the solvent molecules during the first charge and discharge will cause the graphite to fall off, thereby reducing the life of the motor. If it is not handled in time, it will increase the safety hazard. In addition, the graphite electrode is in an oxidizing high-temperature environment for a long time. Under working conditions, a large amount of heat can easily cause the oxidation of the graphite electrode, which directly reduces the durability of the graphite electrode.
[0003] In view of the above-mentioned problems, the present application specifically develops a method for co-processing and preparing pre-treated carbon nanotubes on graphite electrodes. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a graphite electrode and a preparation method thereof, and to specifically develop a method for the coordinated processing and preparation of graphite electrodes by pretreated carbon nanotubes. The pretreated carbon nanotubes have improved dispersion performance due to surface modification, and can directly improve the crystallinity content of the graphite electrode stone after being mixed with graphite to form electrodes, directly playing a synergistic role of additives in enhancing physical and chemical properties, and fully eliminating the interference of other additives such as dispersants on the performance of graphite electrodes during processing.
[0005] In order to achieve the above object, the first aspect of the present invention provides a graphite electrode, which comprises the following raw materials in parts by weight:
[0006] 10 to 100 parts by mass of carbon nanotubes;
[0007] 10 to 100 parts by mass of petroleum needle coke;
[0008] 20 to 50 parts by weight of asphalt;
[0009] The carbon nanotubes are pretreated to make the dispersion degree D of the carbon nanotubes 80% to 95%, preferably 90% to 95%. The pretreatment modifies the surface and enhances the dispersion performance. The pretreated carbon nanotubes are then mixed with the petroleum needle coke and the asphalt to obtain a graphite electrode.
[0010] In the present invention, the carbon nanotubes are agglomerated before pretreatment, and their dispersion D is 10% to 15%. The dispersion D of the carbon nanotubes is measured by measuring the transmittance T by UV-visible spectrophotometer, and the dispersion D is finally calculated and measured by the calculation formula D=(1-T)×100%.
[0011] According to the present invention, the graphite electrode comprises the following raw materials in parts by mass:
[0012] 40-100 parts by mass of carbon nanotubes;
[0013] 40-100 parts by mass of petroleum needle coke;
[0014] 40-50 parts by mass of asphalt.
[0015] In some embodiments of the present invention, pre-treating carbon nanotubes comprises the steps of:
[0016] S11, mixing the carbon nanotubes and the solvent and performing a shaking treatment to obtain a first intermediate;
[0017] S12, removing part of the solvent in the first intermediate to obtain a second intermediate;
[0018] S13, treating the second intermediate in an inactive protective gas atmosphere in a plasma device to obtain the pretreated carbon nanotubes.
[0019] According to the present invention, in step S11, the carbon nanotubes and the solvent are subjected to an oscillation treatment by an ultrasonic device. The purpose of the oscillation treatment is to prepare a carbon nanotube solution and to initially break up the carbon nanotubes that are aggregated together due to molecular forces.
[0020] According to the present invention, the obtained pretreated carbon nanotubes are in powder form.
[0021] In the present invention, the plasma equipment is RF-PECVD (Radio Frequency Plasma-enhanced Chemical Vapor Deposition) independently developed and assembled by Pusan National University in South Korea. For example, when using plasma for reaction, the power can be set to 60 to 80 watts and the treatment time can be 20 to 40 minutes.
[0022] In some embodiments of the present invention, in step S11, the mass ratio of carbon nanotubes to solvent is (10-100):(100-1000), preferably (80-100):(100-150); and / or the solvent is water and / or ethanol.
[0023] In some embodiments of the present invention, in step S12, the mass ratio of carbon nanotubes to solvent in the second intermediate is (10-100): (1-20), preferably (15-25): (1-3). A portion of the solvent in the first intermediate can be removed by filtering, so that the mass ratio of carbon nanotubes to solvent in the second intermediate is (10-100): (1-20). Step S12 removes excess solvent to obtain a high-concentration dispersed solution of carbon nanotubes, thereby preparing for subsequent plasma surface pretreatment.
[0024] In some embodiments of the present invention, in step S13, the plasma equipment is a low-pressure low-frequency sputtering plasma equipment. For example, the low-pressure low-frequency sputtering plasma equipment is an RF-PECVD independently developed and assembled by Pusan National University in South Korea. The purpose of processing in the plasma equipment is to modify the surface of the carbon nanotubes to achieve activation.
[0025] According to the present invention, the plasma used in the plasma treatment is plasma formed by at least one of argon, oxygen and nitrogen.
[0026] According to the present invention, in step S13, the inactive protective gas is nitrogen and / or argon (preferably a mixture of nitrogen and argon). In step S13, the second intermediate is treated in an inactive protective gas atmosphere in order to fully modify the surface of the carbon nanotubes to achieve activation, and plasma can fully improve the solvent affinity of the carbon nanotubes.
[0027] In some embodiments of the present invention, the carbon nanotubes have a diameter of 1-5 μm and a length of 3-20 μm.
[0028] The petroleum-based needle coke in the present invention can come from Maoming Petrochemical Co., Ltd.; the asphalt in the present invention is a petroleum-based asphalt, which can come from Panjin Petrochemical Co., Ltd.
[0029] In the present invention, highly dispersed carbon nanotubes provide a current path network bridge structure for the graphite electrode, and the higher the dispersion, the lower the internal resistance of the electrode, which promotes the uniform distribution of current and significantly improves the first discharge specific capacity. The pretreated carbon nanotubes of the present invention do not contain any other binder, and all substances are directly mixed with needle coke and pitch in the form of powder, which does not affect the dispersion and directly refines the particle size in the form of raw materials. It not only realizes the in-situ purification of carbon nanotubes during the graphitization process, but also directly improves the dispersion stability of carbon nanotubes, the physical properties and chemical properties of the electrode, and saves the use cost of carbon nanotubes.
[0030] The second aspect of the present invention provides a method for preparing the graphite electrode as described in the first aspect above, comprising the following steps:
[0031] S1, pretreating the carbon nanotubes to obtain pretreated carbon nanotubes;
[0032] S2. Processing the raw materials including the pretreated carbon nanotubes, petroleum needle coke and asphalt to obtain a graphite electrode.
[0033] In some embodiments of the present invention, the step S1 of pretreating the carbon nanotubes comprises the following steps:
[0034] S11, mixing the carbon nanotubes with a solvent and performing a shaking treatment to obtain a first intermediate; the solvent is water and / or ethanol;
[0035] S12, removing part of the solvent in the first intermediate to obtain a second intermediate;
[0036] S13, treating the second intermediate in an inactive protective gas atmosphere in a plasma device to obtain the pretreated carbon nanotubes.
[0037] In the present invention, the step S1 of pre-treating the carbon nanotubes (steps S11 to S13) is the same as described above and will not be repeated here.
[0038] In some embodiments of the present invention, step S2 comprises:
[0039] S21, melting the asphalt, mixing it with the petroleum needle coke and the pretreated carbon nanotubes to obtain a mixed material;
[0040] S22, forming the mixed material to obtain a graphite electrode precursor;
[0041] S23, calcining the graphite electrode precursor to obtain the graphite electrode.
[0042] According to the present invention, in step S21, the asphalt is first melted, and then mixed with the petroleum-based needle coke and the pretreated carbon nanotubes, and the temperature of the melted asphalt is maintained to complete the stirring. The present invention has no strict restrictions on the temperature of the asphalt melting and the three raw materials mixing. For example, the temperature of the asphalt melting is 70°C, and the three raw materials are mixed and stirred at 80r / min for 70 minutes.
[0043] According to the present invention, in step S22, the mixed material can be introduced into a mold and pressurized to complete the plastic molding. For example, after the three raw materials are introduced into the mold, the pressure is increased to 20-40Mpa before solidification, and the pressure is maintained for 40min-1h to obtain a graphite electrode precursor.
[0044] According to the present invention, in step S23, the present invention has no strict restrictions on the temperature, heating rate, time, number of calcinations, etc. for calcining the graphite electrode precursor, and those skilled in the art can determine it according to actual conditions. For example, in step S23, calcining the graphite electrode precursor may include: calcining the graphite electrode precursor in reverse under nitrogen protective gas conditions, with a heating rate of 2-5°C / min, and when the temperature is raised to 1000°C, it is maintained for 18 hours, and then the cooling nitrogen gas atmosphere is continued, and it is fully cooled for 80 hours; then heated to 1800°C in a high-temperature furnace under nitrogen protective gas conditions, with a heating rate of 5-10°C / min, and the temperature is raised to 1800°C and maintained for 20 hours, and then the cooling nitrogen gas atmosphere is maintained, and it is fully cooled for 80 hours, and finally a graphite electrode is obtained.
[0045] In some embodiments of the present invention, the method for preparing the graphite electrode comprises the steps of:
[0046] (1) Mix 10-100 parts of carbon nanotubes with water and treat with ultrasonic vibration for 1 hour;
[0047] (2) Filter and remove part of the water, so that the mass ratio of carbon nanotubes to water is (10-100): (1-20)
[0048] (3) placing the carbon nanotubes in a low-pressure, low-frequency sputtering plasma device under a nitrogen and argon gas atmosphere and treating them at a power of 80 W for 20 min;
[0049] (4) Place 20-50 parts of asphalt in a mixing bottle and heat to 180°C to melt, add 10-100 parts of petroleum needle coke and 10-100 parts of treated carbon nanotubes, keep heating at 180°C and stirring at a speed of 80 r / min for 70 minutes;
[0050] (5) introducing the uniformly mixed material into a mold for plastic molding, pressurizing to 20-40 MPa, and maintaining the pressure for 40 min-1 h to obtain a pretreated graphite electrode precursor;
[0051] (6) Under nitrogen protective gas conditions, the graphite electrode precursor was reversely calcined at a heating rate of 2-5°C / min. When the temperature reached 1000°C, it was maintained for 18 hours, and then the cooling nitrogen gas atmosphere was continued and fully cooled for 80 hours;
[0052] (7) Continue heating in a high temperature furnace to 1800°C under a nitrogen atmosphere at a heating rate of 5-10°C / min. When the temperature reaches 1800°C, maintain it for 20 hours, then continue to maintain a cooling nitrogen atmosphere and fully cool it for 80 hours to finally produce a graphite electrode.
[0053] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0054] (1) The graphite electrode and preparation method provided by the present invention can activate the surface of carbon nanotubes, increase the free energy of carbon nanotubes, and fully improve the dispersion of carbon nanotubes through the pretreatment technology of carbon nanotubes; the pretreated carbon nanotubes can be evenly mixed with asphalt and petroleum coke raw materials, reduce the difficulty of surface bonding, directly improve the crystallinity content of graphite electrode stone, directly play a synergistic role of additives in enhancing physical and chemical properties, and fully eliminate the interference of other additives such as dispersants on the performance of graphite electrodes during processing;
[0055] (2) The carbon nanotubes used in the graphite electrode and preparation method thereof provided by the present invention have a uniform length-to-diameter ratio, and the pretreated carbon nanotubes are evenly distributed in the graphite electrode, which fully ensures that cracks in the graphite electrode are reduced during processing and gives full play to the synergistic enhancement effect of the nano-additives;
[0056] (3) The carbon nanotubes used in the graphite electrode and preparation method thereof provided by the present invention have a uniform length-to-diameter ratio, and the pretreated carbon nanotubes are evenly distributed in the graphite electrode, making full use of the excellent electrical conductivity of the carbon nanotubes to form a smooth current path network bridge structure; at the same time, the pretreated carbon nanotubes can achieve a uniform dispersion effect, promoting the uniform distribution of current when the graphite electrode is used;
[0057] (4) The graphite electrode and preparation method thereof provided by the present invention can directly mix the pretreated carbon nanotubes with other raw materials (petroleum-based needle coke and asphalt) and then directly process and calcine to prepare the graphite electrode without the need for other complicated steps, thereby reducing the complexity of the processing technology. DETAILED DESCRIPTION
[0058] The present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the following description.
[0059] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials, reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained through commercial channels or prepared according to the preparation methods disclosed in the prior art.
[0060] In the following examples, the dispersion degree D of the carbon nanotubes without pretreatment is 15%.
[0061] In the present invention, carbon nanotubes are purchased from South Korea's nano carbon enterprise, with a tube diameter of 1-5μm and a length of 3-20μm; petroleum needle coke is purchased from Maoming Petrochemical Co., Ltd.; asphalt is purchased from Liaoning Baolai Chemical Co., Ltd.; the low-pressure and low-frequency sputtering plasma equipment of this application is an RF-PECVD (Radio Frequency Plasma-enhanced Chemical Vapor Deposition) device independently developed and assembled by Pusan National University in South Korea.
[0062] Example 1
[0063] The method for preparing the graphite electrode of this embodiment comprises the following steps:
[0064] (1) 100 parts by weight of carbon nanotubes and 100 parts by weight of water were mixed and subjected to ultrasonic vibration for 1 hour;
[0065] (2) filtering and removing part of the water so that the mass ratio of carbon nanotubes to water is 20:1;
[0066] (3) placing the carbon nanotubes in a low-pressure, low-frequency sputtering plasma device under a mixed gas atmosphere of nitrogen and argon, and treating at a power of 80 W for 30 minutes to obtain pretreated carbon nanotubes; the dispersion degree D of the pretreated carbon nanotubes was measured and calculated to be 95%;
[0067] (4) Place 40 parts by weight of asphalt in a mixing bottle and heat to 180° C. to melt, add 80 parts by weight of petroleum needle coke and 100 parts by weight of the pretreated carbon nanotubes prepared in step (3), keep heating at 180° C. and stirring at a speed of 800 r / min for 1 hour;
[0068] (5) introducing the uniformly mixed materials into a mold for plastic molding, applying a pressure of 30 MPa, and maintaining the pressure for 50 min to obtain a pretreated graphite electrode precursor;
[0069] (6) Under nitrogen protective gas conditions, the graphite electrode precursor was reversely calcined at a heating rate of 2-5°C / min. When the temperature reached 1000°C, it was maintained for 18 hours, and then the cooling nitrogen gas atmosphere was continued and fully cooled for 80 hours;
[0070] (7) Continue to heat to 1800°C in a high temperature furnace under a nitrogen gas atmosphere at a heating rate of 5-10°C / min. When the temperature reaches 1800°C, maintain it for 20 hours, then continue to maintain a cooling nitrogen gas atmosphere and fully cool it for 80 hours, and finally obtain graphite electrode A1.
[0071] Example 2
[0072] The preparation method of the graphite electrode of this embodiment is roughly the same as that of the embodiment, except that in step (3), the plasma used for pretreatment is replaced by plasma formed by argon gas, the processing power of the low-pressure low-frequency sputtering plasma equipment is 80w, the processing time is 40min, and the dispersion degree D of the carbon nanotubes after pretreatment is measured and calculated to be 84%; finally, a graphite electrode A2 is obtained.
[0073] Example 3
[0074] The preparation method of the graphite electrode of this embodiment is roughly the same as that of the embodiment, except that in step (3), the plasma used for pretreatment is replaced by plasma formed by oxygen, the processing power of the low-pressure low-frequency sputtering plasma equipment is 80w, the processing time is 40min, and the dispersion degree D of the carbon nanotubes after pretreatment is measured and calculated to be 80%; finally, a graphite electrode A3 is obtained.
[0075] Example 4
[0076] The preparation method of the graphite electrode of this embodiment is roughly the same as that of the embodiment, except that the amount of carbon nanotubes used is 60 parts by weight; the amount of asphalt used is 50 parts by weight; the amount of petroleum needle coke used is 100 parts by weight, and finally a graphite electrode A4 is prepared.
[0077] Example 5
[0078] The preparation method of the graphite electrode of this embodiment is roughly the same as that of Embodiment 1, except that the amount of carbon nanotubes used is 40 parts by weight; the amount of asphalt used is 40 parts by weight; the amount of petroleum needle coke used is 40 parts by weight, and graphite electrode A5 is prepared.
[0079] Example 6
[0080] The preparation method of the graphite electrode of this embodiment is roughly the same as that of the embodiment, except that the amount of carbon nanotubes used is 10 parts by weight; the amount of asphalt used is 20 parts by weight; the amount of petroleum needle coke used is 50 parts by weight, and graphite electrode A6 is prepared.
[0081] Comparative Example 1
[0082] The preparation method of the graphite electrode of comparative example 1 is substantially the same as that of the embodiment, except that: the carbon nanotubes are not subjected to the pretreatment of steps (1) to (3), and the pretreated carbon nanotubes in step (4) are replaced by unpretreated carbon nanotubes; and the graphite electrode D1 is obtained by the steps (4) to (7).
[0083] Comparative Example 2
[0084] 100 parts of petroleum coke particles, 15 parts of needle coke, 5 parts of calcium oxide, 38 parts of asphalt and 35 parts of carbon nanotube dispersion. The carbon nanotubes are a mixture of agglomerated carbon nanotubes and array tubes, the diameter of the agglomerated carbon nanotubes is 10-30nm, the length is 3-50μm, the particle size D50 is 1-3μm, the diameter of the array tubes is 8-20nm, the length is 1mm-1m, the particle size D50 is 5-10μm, and the mixing mass ratio is 1:1; the carbon nanotube dispersion is prepared by sand grinding carbon nanotubes, toluene and polyvinyl pyrrolidone with a nano sand mill, and the weight ratio of carbon nanotubes, toluene and polyvinyl pyrrolidone is 8:70:8.
[0085] The preparation method of the graphite electrode of this comparative example comprises the steps of:
[0086] First, 100 parts of petroleum coke particles, 55 parts of carbon nanotubes, 60 parts of needle coke, and 9 parts of calcium oxide are introduced into a kneading pot, heated to 132°C, and kneaded for 70 minutes. 40 parts of asphalt are weighed, heated to 175°C in a liquid evaporation recovery system to melt, 90 parts of carbon nanotube dispersion are added, stirred and mixed by a high-force stirrer, and then added to the kneading pot of step (1), the kneading pot is controlled to be heated to 163°C, the stirring speed of the kneading pot is 1650r / min, and the heat is maintained for kneading for 60 minutes; after kneading, the materials are introduced into a molding mold, pressurized to 20MPa, and maintained at pressure for 55 minutes to obtain a graphite electrode D2.
[0087] Comparative Example 3
[0088] 100 parts of petroleum coke particles, 15 parts of needle coke, 5 parts of calcium oxide, and 38 parts of asphalt.
[0089] The preparation method of the graphite electrode of this comparative example comprises the steps of:
[0090] First, 100 parts of petroleum coke particles, 15 parts of needle coke, and 5 parts of calcium oxide were introduced into a kneading pot, heated to 135°C, and kneaded for 65-75 minutes; 38 parts of asphalt were weighed, heated to 170°C in a liquid evaporation recovery system to melt, and then added to the kneading pot, and the kneading pot was controlled to heat up to 160°C, and the stirring speed of the kneading pot was 1550r / min. After the kneading was completed, the material was introduced into a molding mold, pressurized to 15MPa, and maintained for 50 minutes to obtain a graphite electrode blank to be baked. Under nitrogen protective atmosphere conditions, the graphite electrode blank was baked at a heating rate of 5°C / min, maintained at a maximum temperature of 1450°C for 24, and then cooled naturally. After cooling for 75 hours, the graphite electrode D3 was finally obtained.
[0091] Test Case
[0092] The true density is measured by passing helium through a true density tester (G-DenPyc 3900) to preheat to 35°C for 30 min, then filling an appropriate sample cell with a sample that is not less than 2 / 3 of the sample cell volume, and measuring according to the instructions of the true density tester;
[0093] The flexural strength is measured by sampling carbon materials according to the GB / T1427-2000 method and in accordance with the GB / T3074.1-2021 standard;
[0094] The elastic modulus is measured by sampling carbon materials according to the GB / T1427-2000 method and in accordance with the GB / T3074.2-2021 standard method;
[0095] Preparation of the first discharge specific capacity test sample: Super-P carbon black is the conductive agent, SBR is the binder, and they are mixed evenly at a mass ratio of 92:5:3, and then adjusted to a paste with deionized water as the solvent. The paste is evenly coated on a 9-micron thick copper foil to form a 1.0 cm × 1.5 cm pole piece, and then rolled to the required thickness of the pole piece after drying at 45°C, and dried at 100°C in vacuum for 8 hours. The material is then made into a rectangular electrode and dried at 100°C in vacuum for 8 hours. The battery program-controlled tester (LAND-CT2001A) is used at 23±2°C, a voltage range of 0.005~5V, and a charge and discharge current density of 80mA / g, and a 1mol / L LiPF6 EC / EMC (volume ratio of 1:1) solution is used as the electrolyte to test the charge and discharge performance of the experimental battery.
[0096] The test results are shown in Table 1.
[0097]
[0098]
[0099] By comparing Examples 1-3 with Comparative Example 1, it is found that although the dispersions D of the pretreated carbon nanotubes obtained in the inactive protective gas atmosphere are different, they are all sufficiently improved and are higher than the dispersion of the untreated carbon nanotubes.
[0100] As can be seen from Table 1 above, by comparing Examples 1-6 with Comparative Examples 1-3, the flexural strength, elastic modulus and first discharge specific capacity of the graphite electrode A1 obtained after pretreatment are significantly improved, indicating that the addition of pretreated carbon nanotubes has a significant effect on enhancing the physical and electrical properties of the graphite electrode.
[0101] The present invention improves the material density of the graphite electrode by adding carbon nanotubes, and the aspect ratio plays an enhancing role: the resistivity of the graphite electrode is reduced while the density of the graphite electrode is increased, and the flexural strength and elastic modulus are enhanced.
[0102] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A graphite electrode comprising the following raw materials in parts by weight: 10 to 100 parts by mass of carbon nanotubes; 10 to 100 parts by mass of petroleum needle coke; 20 to 50 parts by weight of asphalt; in, The carbon nanotubes are pretreated to make their dispersion degree D 80% to 95%, and the pretreated carbon nanotubes are mixed with the petroleum needle coke and the asphalt to form the graphite electrode.
2. The graphite electrode according to claim 1, characterized in that The graphite electrode comprises the following raw materials in parts by mass: 40 to 100 parts by weight of carbon nanotubes; 40-100 parts by mass of petroleum needle coke; 40-50 parts by mass of asphalt.
3. The graphite electrode according to claim 1 or 2, characterized in that: The pretreatment of carbon nanotubes includes the following steps: S11, mixing the carbon nanotubes and the solvent and performing a shaking treatment to obtain a first intermediate; S12, removing part of the solvent in the first intermediate to obtain a second intermediate; S13, treating the second intermediate in a plasma device under an inactive protective gas atmosphere to obtain the pretreated carbon nanotubes.
4. The graphite electrode according to claim 3, characterized in that: In the step S11, the mass ratio of the carbon nanotubes to the solvent is (10-100): (100-1000); And / or, the solvent is water and / or ethanol.
5. The graphite electrode according to claim 3 or 4, characterized in that: In the step S12, the mass ratio of the carbon nanotubes in the second intermediate to the solvent is (10-100):(1-20).
6. The graphite electrode according to any one of claims 3 to 5, characterized in that: In the step S13, the plasma equipment is a low-pressure and low-frequency sputtering plasma equipment.
7. The graphite electrode according to any one of claims 3 to 6, characterized in that: In the step S13, the plasma used for the treatment by the plasma equipment is a plasma formed by at least one of argon, oxygen and nitrogen; And / or, the inactive protective gas is nitrogen and / or argon.
8. The graphite electrode according to any one of claims 1 to 7, characterized in that: The carbon nanotubes have a diameter of 50 to 450 μm and a length of 300 to 500 μm.
9. The method for preparing the graphite electrode according to any one of claims 1 to 8, comprising the following steps: S1, pretreating the carbon nanotubes to obtain pretreated carbon nanotubes; S2. Processing the raw materials including the pretreated carbon nanotubes, petroleum needle coke and asphalt to obtain a graphite electrode.
10. The preparation method according to claim 9, characterized in that: The step S2 comprises: S21, melting the asphalt, mixing it with the petroleum needle coke and the pretreated carbon nanotubes to obtain a mixed material; S22, forming the mixed material to obtain a graphite electrode precursor; S23, calcining the graphite electrode precursor to obtain the graphite electrode.